Building Up Quarternary Stereocenters of Chromans by Asymmetric Redox Organocatalysis: A New Entry to Vitamin E. Issue 52 (13th November 2014) - Netscher, Thomas
<x xml:space="preserve">Abstract</x> High‐turnover catalysis offers a novel concept for the efficient chemo‐ and enantioselective preparation of chroman intermediates, which are useful for the synthesis of tocopherols (vitamin E components) and other biologically active compounds. A chiral ammonium iodide catalyst mediates the cycloetherification in combination with a cooxidant and an inorganic base in excellent yield and up to 93 % ee. OTs=para‐toluenesulfonyl.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>